Use of tannin as a photosensitizer in photodynamic therapy against Enterococcus faecalis (Research, Society and Development, 2021)
The present study aimed to evaluate the microbial reduction after photodynamic therapy as an adjunct to chemical-surgical preparation (CSP), using the hydrolysable tannin as a photosensitizer in root canals of bovine teeth infected with Enterococcus faecalis. 60 teeth, divided into six groups: group NaOCl, only NaOCl 2.5% was used; group PDT/MB, PDT with methylene blue as a photosensitizer was used; group Tan, only tannin was used as photosensitizer; group PDT/Tan, where only tannin PDT was used as photosensitizer; group NaOCl/PDT/Tan, NaOCl 2.5% was associated to tannin PDT; and group NaOCl/PDT/MB, NaOCl 2.5% was associated to PDT with methylene blue. For PDT, 3ml of the photosensitizer was used at a 0,005% concentration for 5min (pre- irradiation time). For the irradiation, a portable semiconductor laser (Laser DUO®, GaAlAs, InGaAlP) was used, wavelength of 660 nm, power of 100 mW, totaling 1.8 J of energy and 180 seg of irradiation time. Three microbiological collections were performed, called initial (before SCP), intermediate (after CSP) and final (7 days after CSP). After the collections, plating was done for counting the CFU's. The results were expressed as statistical measures: mean, standard deviation, median, quartiles and minimum and maximum values​​. The F-test (ANOVA) for multiple comparisons and the Tamanhe of Kruswal-Wallis test were used. The verification of the hypothesis of normality was performed using the Shapiro-Wilk test. The significance level was set at 0,05. It was concluded that photodynamic therapy, using hydrolysable tannin as a photosensitizer, proved to be effective as an adjunct to chemical-surgical preparation in microbial reduction.